Plant glyco-biotechnology on the way to synthetic biology - Loos, Andreas; Steinkellner, Herta (Frontiers in Plant Science, 2014)
Plants are increasingly being used for the production of recombinant proteins. One reason is that plants are highly amenable for glycan engineering processes and allow the production of therapeutic proteins with increased efficacies due to optimized glycosylation profiles. Removal and insertion of glycosylation reactions by knock-out/knock-down approaches and introduction of glycosylation enzymes have paved the way for the humanization of the plant glycosylation pathway. The insertion of heterologous enzymes at exactly the right stage of the existing glycosylation pathway has turned out to be of utmost importance for optimal results. To enable such precise targeting chimeric enzymes have been constructed. In this short review we will exemplify the importance of correct targeting of glycosyltransferases, we will give an overview of the targeting mechanism of glycosyltransferases, describe chimeric enzymes used in plant N-glycosylation engineering and illustrate how plant glycoengineering builds on the tools offered by synthetic biology to construct such chimeric enzymes.